PRE-SERVICE TEACHERS’ SYMBOLIC-VISUAL REPRESENTATION SKILLS IN ADDING AND SUBTRACTING FRACTIONS - Arwan Mhd. Said; Purwanto Purwanto; Erry Hidayanto; Rustanto Rahardi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
The current study attempted to describe pre-service teachers’ symbolic-visual representation skills in adding and subtracting fractions. It specifically aimed to analyze the teachers’ ability to construct either a symbolic or visual representation in fraction operations. A case study was conducted by involving 17 fifth-semester students who were enrolled in a teacher training course at one of universities in Ternate, Indonesia. The participants consisted of two males and fifteen females. The study data were gathered using a fraction problem-solving test. The results showed that: 1) the majority of participants succeeded in performing fraction operations and making representations by adding and subtracting fractions; 2) the participants demonstrated proficiency in executing fraction operations but showed poor ability in generating different representations of fractions; 3) the participants were more successful in creating visual representation for fraction addition compared to fraction subtraction. The participants also excelled in constructing circle models as visual representations, outperforming other visual representation models such as number lines, rectangular models for transition situations, and numerical representations of mixed fractions.